Context matters in understanding the vulnerability of women- perspectives from southwestern Uganda. - Murembe, Neema; Kyomuhangi, Teddy; Manalili, Kimberly; Beinempaka, Florence; Nakazibwe, Primrose; Kyokushaba, Clare; Tibanyendera, Basil; Brenner, Jennifer L.; Turyakira, Eleanor (Archives of Public Health., 2021)
Background: Vulnerability at the individual, family, community or organization level affects access and utilization of health services, and is a key consideration for health equity. Several frameworks have been used to explore the concept of vulnerability and identified demographics including ethnicity, economic class, level of education, and geographical location. While the magnitude of vulnerable populations is not clearly documented and understood, specific indicators, such as extreme poverty, show that vulnerability among women is pervasive. Women in low and middle-income countries often do not control economic resources and are culturally disadvantaged, which exacerbates other vulnerabilities they experience. In this commentary, we explore the different understandings of vulnerability and the importance of engaging communities in defining vulnerability for research, as well as for programming and provision of maternal newborn and child health (MNCH) services. Methodology: In a recent community-based qualitative study, we examined the healthcare utilization experiences of vulnerable women with MNCH services in rural southwestern Uganda. Focus group discussions were conducted with community leaders and community health workers in two districts of Southwestern Uganda. In addition, we did individual interviews with women living in extreme poverty and having other conventional vulnerability characteristics. Findings and discussion: We found that the traditional criteria of vulnerability were insufficient to identify categories of vulnerable women to target in the context of MNCH programming and service provision in resource limited settings. Through our engagement with communities and through the narratives of the people we interviewed, we obtained insight into how nuanced vulnerability can be, and how important it is to ground definitions of vulnerability within the specific context. We identified additional aspects of vulnerability through this study, including: women who suffer from alcoholism or have husbands with alcoholism, women with a history of home births, women that have given birth only to girls, and those living on fishing sites. Conclusion: Engaging communities in defining vulnerability is critical for the effective design, implementation and monitoring of MNCH programs, as it ensures these services are reaching those who are most in need.
Keywords: Vulnerability; MNCH programming; Diversity; MNCH interventions; Community engagement; Context matters; Context